Service providers’ willingness to change as innovation inductor in services : validating a scale - Moreira, Marina Figueiredo (2016)
This study explores the willingness of service providers to incorporate changes suggested by clients altering previously planned services during its delivery, hereby named Willingness to Change in Services [WCS]. We apply qualitative research techniques to map seven dimensions related to this phenomenon: Client relationship management; Organizational conditions for change; Software characteristics and development; Conditions affecting teams; Administrative procedures and decision-making conditions; Entrepreneurial behavior; Interaction with supporting organizations. These dimensions have been converted into variables composing a WCS scale later submitted to theoretical and semantic validations. A scale with 26 variables resulted from such procedures was applied on a large survey carried out with 351 typical Brazilian software development service companies operating all over the country. Data from our sample have been submitted to multivariate statistical analysis to provide validation for the scale. After factorial analysis procedures, 24 items have been validated and assigned to three factors representative of WCS: Organizational Routines and Values - 12 variables; Organizational Structure for Change - 6 variables; and Service Specificities - 6 variables. As future contributions, we expect to see further testing for the WCS scale on alternative service activities to provide evidence about its limits and contributions to general service innovation theory.